An Owner-Independent Investigation of Diabetes Alert Dog Performance - Wilson, Clara; Morant, Steve; Kane, Sarah; Pesterfield, Claire; Guest, Claire; Rooney, Nicola J. (Frontiers in Veterinary Science, 2019)
Objective: To quantify Diabetes Alert Dog (DAD) performance by using owner-independent measures. Research Design and Methods: Eight owners of accredited DADs used a FreeStyle Libre Flash Glucose Monitoring System (FGMS). Concurrent CCTV footage was collected for between 5 and 14 days in each owner’s home or workplace. The footage was blind-coded for dogs’ alerting behaviours. We calculated the sensitivity and positive predictive values (PPV) of dogs’ alerts to out-of-range (OOR) episodes. Ratings for 11 attributes describing participant’s lifestyle and compliance (taken from each dog’s instructor) and the percentage of DAD alerts responded to by the owner as per training protocol (taken from CCTV footage) were assessed for association with dog performance. Results: Dogs alerted more often when their owners’ glucose levels were outside vs. inside target range (hypoglycaemic 2.80-fold, p = 0.001; hyperglycaemic 2.29-fold, p = 0.005). Sensitivity to hypoglycaemic episodes ranged from 33.3% to 91.7%, the mean was 55.9%. Mean PPV for OOR episodes was 69.7%. Sensitivity and PPV were associated with aspects of the dog and owner’s behaviour, and the owner’s adherence to training protocol. Conclusions: Owner-independent methods confirm that some dogs alert to hypo- and hyperglycaemic events accurately, but performance varies between dogs. We find that DAD performance is affected by traits and behaviours of both the dog and owner. Combined with existing research showing the perceived psychosocial value and reduced critical health care needs of DAD users, this study supports the value of a DAD as part of a diabetes care plan. It also highlights the importance of their initial selection, ongoing training and continued monitoring to ensure optimal performance.